Communication and digital inclusion in rural areas: use of Whatsapp application as a means of communication and business management (Desenvolvimento em Questão, 2022)
With the phenomenon of technological advancement in the areas of Information and Communication Technology (ICTs), a new and complex path opens up for social interactions, access to information and dissemination of ideas. It is no exaggeration to say that the advancement of ICTs has given voice to a population, previously silent. Although this technology is more accessible to the urban environment, the insertion of communication tools and internet networks in rural areas has enabled the development of new forms of communication, entertainment and business. In this sense, the present work aims to analyze the relationship of family farmers in the municipality of Vitorino / PR with the inclusion of digital devices, in particular the use of the WhatsApp application as a means of communication and business management. To this end, twenty interviews were conducted with family farmers in the municipality. The results show that the WhatsApp application has expanded beyond communication, it has become a form of property management, a quick and flexible way that makes it possible to keep in touch with companies and those responsible for technical assistance. However, even with the installation of networks in rural areas, with a good signal quality and the insertion of digital devices, such as computers and smartphones (cell phones), there is still a digital exclusion of a portion of farmers who, in turn, is caused by restricted knowledge about the functionality of these devices and platforms
Keywords: WhatsApp. Communication. Digital Inclusion. Management. Contryside.